1999
DOI: 10.1126/science.284.5411.128
|View full text |Cite
|
Sign up to set email alerts
|

Clinoenstatite in Alpe Arami Peridotite: Additional Evidence of Very High Pressure

Abstract: Observations by transmission electron microscopy show that lamellae of clinoenstatite are present in diopside grains of the Alpe Arami garnet lherzolite of the Swiss Alps. The simplest interpretation of the orientation, crystallography, and microstructures of the lamellae and the phase relationships in this system is that the lamellae originally exsolved as the high-pressure C-centered form of clinoenstatite. These results imply that the rocks were exhumed from a minimum depth of 250 kilometers before or durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
74
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 41 publications
(23 reference statements)
7
74
0
Order By: Relevance
“…The structural transformation from enstatite belonging to the C2/c space group (HT-CLEN and HP-CLEN) to the P2 1 /c modification (LTLP-CLEN) will lead to the formation of antiphase domains (APDs) due to the loss of a translational symmetry component (e.g., Bozhilov et al 1999). …”
mentioning
confidence: 99%
“…The structural transformation from enstatite belonging to the C2/c space group (HT-CLEN and HP-CLEN) to the P2 1 /c modification (LTLP-CLEN) will lead to the formation of antiphase domains (APDs) due to the loss of a translational symmetry component (e.g., Bozhilov et al 1999). …”
mentioning
confidence: 99%
“…Despite considerable controversy, subsequent experiments under these conditions have confirmed that Ͼ1 vol % of TiO 2 can be accommodated in olivine (46,47). The additional observation of exsolved Ca-poor pyroxene displaying antiphase domains in diopside (8,48,49) also supports the idea of an extremely deep origin (Ͼ300 km) for the Alpe Arami garnet peridotite.…”
Section: Microstructures Of Vhp Mineralsmentioning
confidence: 76%
“…Intergrowths of ortho-and clinoenstatite lamellae are common within Chinese orogenic garnet peridotites. Clinoenstatite lamellae in orthoenstatite may have formed either by inversion from orthoenstatite or by a displacive transformation from VHP clinoenstatite during decompression (8,12). Experiments indicate that orthoenstatite transforms to VHP clinoenstatite at P Ͼ 8 GPa, 900°C, corresponding to a mantle depth of Ϸ300 km (e.g., refs.…”
Section: Microstructures Of Vhp Mineralsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated that continental crust can be subducted to depths in excess of at least 80 km, possibly to depths of 200 to 350 km (Xu et al, 1992;Yang et al, 1993;Dobrzhinetskaya et al, 1996;Bozhilov et al, 1999;Ye et al, 2000;Zheng, 2003;Liu et al, 2007aLiu et al, , 2008a. During the deep subduction, continental crust underwent high-pressure (HP) to ultrahigh-pressure (UHP) metamorphism and resulted in the formation of various HP and UHP metamorphic rocks in the orogen.…”
Section: Introductionmentioning
confidence: 99%